Analysis Factor Of Saving Behavior Of An Indonesian For Emergency Fund During Covid-19 Pandemic - Roy Poan; Febby Permatasari; Farida Komalasari (International Journal of Family Business Practices, 2021)
Purpose – The objective of this study is to find whether the independent variable, which is financial literacy, attitude towards saving, subjective norms, family socialization has a significant impact on the mediating variable, which is saving intention during the pandemic situation. Researchers also intrigues to find whether saving intention has a significant impact on the dependent variable which is saving behavior in Indonesia at current pandemic.Design/methodology/approach – This research study was conducted using a quantitative method using probability sampling, in which the primary data was collected from the questionnaire filled by 312 Indonesian from age  >17 to <51 years old (productive age). The questionnaire was analyzed using validity and reliability test. The validity and reliability test found that all questions (30 questions) are valid and reliable and can be processed further. The hypotheses and research model of this study were tested using Structural Equation Model.Findings – The results of the survey show that saving intention is affected by saving behavior. In addition, saving intention is influenced by the attitude towards saving, subjective norm, family socialization. Moreover, the financial literacy toward saving intention is not related.Originality/value – The originality of this study is the first research integrating financial literacy, attitude towards saving, subjective norm, and family socialization, mediating by saving intention toward saving behavior in Indonesia